2016
DOI: 10.1161/circimaging.116.004984
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial and Left Atrial Appendage 4D Blood Flow Dynamics in Atrial Fibrillation

Abstract: Background Atrial 4D flow MRI was employed for the characterization of left atrial (LA) and left atrial appendage (LAA) flow dynamics in patients with atrial fibrillation (AF). Methods and Result 4D flow MRI measured in-vivo 3D blood flow velocities in 60 AF patients and 15 controls. Anatomic maps of LA and LAA stasis and velocity were calculated to quantify atrial peak velocity, mean velocity, and stasis (velocities<0.1m/s). In a sub-study with 30 AF patients, 4D flow metrics were compared to Doppler transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 32 publications
6
87
0
Order By: Relevance
“…In fact, though transthoracic (TTE) and transoesophageal echocardiography (TEE) are available in the clinic to measure the blood flow velocity in both the LA and the LAA, both techniques can only provide average information on the velocity magnitude and direction in the sampling volume, without being able to give detailed spatial 3D information on the local flow conditions (30, 31). Ideally, 4D flow MR could provide similar information as the CFD analysis, but the spatial resolution, typically larger than 1 mm voxel, is not sufficient to assess a small region such as the LAA, and is thus not yet suitable for clinical applications (32). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, though transthoracic (TTE) and transoesophageal echocardiography (TEE) are available in the clinic to measure the blood flow velocity in both the LA and the LAA, both techniques can only provide average information on the velocity magnitude and direction in the sampling volume, without being able to give detailed spatial 3D information on the local flow conditions (30, 31). Ideally, 4D flow MR could provide similar information as the CFD analysis, but the spatial resolution, typically larger than 1 mm voxel, is not sufficient to assess a small region such as the LAA, and is thus not yet suitable for clinical applications (32). …”
Section: Discussionmentioning
confidence: 99%
“…For human MRI, IRB approval and informed consent were obtained from all 4D flow MRI study participants. The specifics of image acquisition and analysis were as previously described (Markl et al, 2012, 2016). Studies were performed on 8 healthy volunteers (mean age: 24±1.8 years; four females and four males, heart rate 63.5±beats per minute, LV ejection fraction (EF) % 65.3±2.1).…”
Section: Methodsmentioning
confidence: 99%
“…12 4D flow MRI evaluation of left atrial (LA) hemodynamics has been reported. [13][14][15] Some of regions: the junction between the LA and each of the four PVs (LA-PV), and the LSPV stump. The average blood flow velocity during one cardiac cycle was measured in each VOI.…”
Section: Innovative Clinical Image Introductionmentioning
confidence: 99%